Синус представление центрально-симметричных выпуклых тел - Р. Г. Арамян (Հայաստանի ԳԱԱ)
В статье изучается проблема синус-представления для опорной функции центрально-симметричного выпуклого тела. The problem of the sine representation for the support function of a centrally symmetric convex bodies is studied.
Keywords: Mathematics; Science; Geometry; Trigonometry; Topology